2022
DOI: 10.1002/smll.202200038
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Nanodelivery System‐Generated 1O2 Mediates Tumor Vessel Normalization by Activating Endothelial TRPV4‐eNOS Signaling

Abstract: Tumor microenvironment (TME)‐responsive intelligent photodynamic therapy (PDT) systems have attracted increasing interest in anticancer therapy, due to their potential to address significant and unsatisfactory therapeutic issues, such as limited tissue penetration, inevitable normal tissue damage, and excessive impaired vessels. Here, an H2O2‐triggered intelligent LCL/ZnO PDT nanodelivery system is elaborately designed. LCL/ZnO can selectively regulate tumor‐derived endothelial cells (TECs) and specifically ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 41 publications
1
19
0
Order By: Relevance
“…As shown in Figure I, both ZnO-LD NPs and ZnO NPs could produce oxygen, and oxygen production increased over time, while H 2 O 2 solutions cannot generate oxygen. We previously investigated and confirmed that ZnO NPs can relieve hypoxia at the tumor site and normalize tumor vessels . Considering the present results, we suggested that ZnO-LD NPs could have potential application in tumor vascular normalization therapy.…”
Section: Resultssupporting
confidence: 74%
See 3 more Smart Citations
“…As shown in Figure I, both ZnO-LD NPs and ZnO NPs could produce oxygen, and oxygen production increased over time, while H 2 O 2 solutions cannot generate oxygen. We previously investigated and confirmed that ZnO NPs can relieve hypoxia at the tumor site and normalize tumor vessels . Considering the present results, we suggested that ZnO-LD NPs could have potential application in tumor vascular normalization therapy.…”
Section: Resultssupporting
confidence: 74%
“…We previously investigated and confirmed that ZnO NPs can relieve hypoxia at the tumor site and normalize tumor vessels. 43 Considering the present results, we suggested that ZnO-LD NPs could have potential application in tumor vascular normalization therapy.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…As mentioned above, many researchers have reported visible/NIR mediated PDT of ZnO-based nanomaterials for antimicrobial infection, inflammation regulation and antitumor therapy. 62–64…”
Section: Design and Biomedical Applications Of Single Exogenous Stimu...mentioning
confidence: 99%